Kto to, kto tu, kto tam - Gomóła, Anna (Er(r)go. Teoria - Literatura - Kultura, 2003)
This brief essay, inspired by Stanisław Sojka's Fracha, is concerned with the issues of self-knowledge, identity and locality.